2017
DOI: 10.3928/19382359-20170117-01
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases and Immunizations in International Adoption

Abstract: Children who are adopted internationally have an increased risk of infectious diseases due to endemic conditions and variable access to preventive health care, such as vaccines, in their country of origin. Pediatricians and other providers who care for children should be familiar with the recommended screening for newly arrived international adoptees. Testing for gastrointestinal pathogens, tuberculosis, hepatitis, syphilis, and HIV should be routinely performed. Other endemic diseases and common skin infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…25 Therefore, all internationally adopted children need to undergo screening evaluations based on the risks presented by their previous life circumstances, including health risks specific to country of origin. 18,[43][44][45][46]…”
Section: Initial History and Review Of Medical Recordsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Therefore, all internationally adopted children need to undergo screening evaluations based on the risks presented by their previous life circumstances, including health risks specific to country of origin. 18,[43][44][45][46]…”
Section: Initial History and Review Of Medical Recordsmentioning
confidence: 99%
“…For those adopted domestically, testing is recommended for children with definite or unknown exposure to and/or risk for tuberculosis, HIV, HBV, and sexually transmitted infections. 18,45,46,56,58 Other tests can be considered on an individual basis. 18,45,46,56,58 Children, whether domestically or internationally adopted, may be at risk for iron, calcium, and vitamin D deficiency secondary to past dietary inadequacies.…”
Section: Referral For Diagnostic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Infectious diseases are commonly reported in internationally adopted children (IAC) (1), and their need for rapid, cautious, and thorough screenings has been underlined by several authors (1–5). A recent Italian study indicated that clinical conditions affecting IAC, ranging from congenital malformations, to complex infectious diseases, such as tuberculosis infection (observed in 15% of children included) and parasitosis (in more than 20%), to non-severe and easily treatable infections, such as Molluscum contagiosum and fungal skin infections, have been frequently reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of infectious diseases is crucial both for the optimal management of IAC and to reduce risk of transmission to the community (1, 6, 7). Cases of transmission of the Hepatitis A and Hepatitis B viruses, scabies, tuberculosis, Tinea capitis / corporis , and measles to adoptive families have been reported in the literature (1, 6, 7).…”
Section: Introductionmentioning
confidence: 99%